Potassium Magnesium Citrate Is Superior to Potassium Chloride in Reversing Metabolic Side Effects of Chlorthalidone - Vongpatanasin, Wanpen; Giacona, John M; Pittman, Danielle; Murillo, Ashley; Khan, Ghazi; Wang, Jijia; Johnson, Talon; Ren, Jimin; Moe, Orson W; Pak, Charles C Y (Hypertension (Dallas, Tex. 1979), 2023)
Thiazide diuretics (TD) are the first-line treatment of hypertension because of its consistent benefit in lowering blood pressure and cardiovascular risk. TD is also known to cause an excess risk of diabetes, which may limit long-term use. Although potassium (K) depletion was thought to be the main mechanism of TD-induced hyperglycemia, TD also triggers magnesium (Mg) depletion. However, the role of Mg supplementation in modulating metabolic side effects of TD has not been investigated. Therefore, we aim to determine the effect of potassium magnesium citrate (KMgCit) on fasting plasma glucose and liver fat by magnetic resonance imaging during TD therapy. Accordingly, we conducted a double-blinded RCT in 60 nondiabetic hypertension patients to compare the effects of KCl versus KMgCit during chlorthalidone treatment. Each patient received chlorthalidone alone for 3 weeks before randomization. Primary end point was the change in fasting plasma glucose after 16 weeks of KCl or KMgCit supplementation from chlorthalidone alone. The mean age of subjects was 59±11 years (30% Black participants). Chlorthalidone alone induced a significant rise in fasting plasma glucose, and a significant fall in serum K, serum Mg, and 24-hour urinary citrate excretion (all <0.05). KMgCit attenuated the rise in fasting plasma glucose by 7.9 mg/dL versus KCl ( <0.05), which was not observed with KCl. There were no significant differences in liver fat between the 2 groups. KMgCit is superior to KCl, the common form of K supplement used in clinical practice, in preventing TD-induced hyperglycemia. This action may improve tolerability and cardiovascular safety in patients with hypertension treated with this drug class.